Risk based recall interval for caries management amongst 11-12 year old Pakistani children / Muhammad Taqi - Muhammad, Taqi (2019)
In Pakistan, there are minimal resources allocated for primary dental care, and this has contributed to the high prevalence of dental caries. The mean DMFT score amongst 12-year-old Pakistani children is low, ranging from 1.2 to 2.5, which suggests a slow caries progression. This makes the traditional six-month recall interval inappropriate for caries management for this population. To indirectly overcome the problem of limited resources, the logical approach is to adopt risk-adjusted patient-centred strategies as dental visits made at regular intervals may increase treatment cost, are time-consuming, and may create supplier-induced demand. Recall interval periods on the bases of risk assessment has been recommended with extended period proposed for individuals with low caries risk, and shorter period for individuals identified as high risk for caries. Objectives: This study aimed to recommend the appropriate recall interval period for caries management among 11-12-year Pakistani school children. The specific objectives were to determine the caries risk levels using reduced Cariogram and caries risk predictors in 11-12-year-old Pakistani school children, to assess the agreement on caries detection rate between the modified International Caries Detection and Assessment System and the WHO methods, to determine the predictability of reduced Cariogram, and to determine the rate of caries progression over an 18-month period using the WHO and ICDAS methods. Based on the data obtained, a recommendation on the appropriate dental recall interval for 11-12-year-old Pakistani school children will be made. Material and Methods: A prospective longitudinal study of 18-month duration was conducted from May 2016 to October 2017 using convenient sampling in seven schools of the Bhakkar city of Punjab, Pakistan. A pilot study was conducted to evaluate the acceptability of the research instruments. In this study, a three-day prospective diet diary iv was used to record diet content. A reduced Cariogram program was used to assess the childrenï¿½s caries risk level. Intraoral assessments were performed using WHO and modified ICDAS methods. Caries progression rate was estimated using adjusted caries increment (ADJCI) at non-cavitated and cavitated thresholds. The predictability of reduced Cariogram was tested using the Receiver Operating Characteristic (ROC) analysis. The recommendations of caries recall interval was made by comparing the mean caries increment at baseline with the mean caries increment that occurred at all follow?ups, within risk categories, on cavitated and non-cavitated lesions. Results: The reduced Cariogram program identified 40% of children as low, 30.5% as medium and 29.7% as high caries risk. Past caries experience and cariogenic food intake before bedtime were identified as significant predictors of caries risk. The predictability of the reduced Cariogram was 0.63 at 6 months, 0.65 at 12 month and 0.70 at 18 months. There was no significant difference in the values of DMFS/DMFT and prevalence of dental caries of the WHO method as compared to the modified ICDAS II at cut-off 2. At cut-off 3-6 (cavitated lesions), significant mean caries increment was observed in the high-risk category as compared to low and medium risk categories at all follow-ups. At cut-off A-6 (both cavitated and non-cavitated lesions), significant mean caries increment was observed in all risk categories at all follow-ups. Based on aforementioned findings, recall intervals for caries management in cavitated lesion is 12 months for low and medium-risk children, and six months for high-risk Pakistani 11-12-year-old children respectively. On the other hand, recall intervals for caries management in both non?cavitated and cavitated lesion is 6 months for low, medium-risk and high-risk Pakistani 11-12-year-old children respectively. v Conclusion: Depending on the level of caries risk and the clinical features of the carious lesions (cavitated or non-cavitated), the recommended caries recall interval for Pakistani children aged 11-12 years old varies from 6 to 12 months. Keywords: Dental recall, Caries risk assessment, ICDAS, DMFT, Caries incremen